2012
DOI: 10.1007/s11746-012-2039-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Contents in Fractions of Neutral Lipids and Phospholipids of Fillets of Tilapia Treated with Flaxseed Oil

Abstract: The fatty acid composition in fractions of neutral lipids (NL) and phospholipids (PL) of the lipid content of muscle tissue of tilapia (Oreochromis niloticus) fed diets enriched with 7% of flaxseed oil was evaluated. Lipid profiles were evaluated every 15 days over 90 days. NL were predominant, with saturated and monounsaturated fatty acids being the major ones, and the PL fraction showed a great amount of polyunsaturated fatty acids (PUFA). The PUFA/SFA ratio values were lower in the NL fraction, ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The moisture and ash percentages (Table 4) of the muscle tissues of the animals in the two treatments were close to the rates given by Simões 22 and Tonial 23 in their research on the tilapia muscle tissue. The CP rates at the end of the current experiment were close to those given in the study by Visentainer 24 in juvenile tilapia, with rates ranging between 19.8 and 20.9%.…”
Section: Discussionsupporting
confidence: 79%
“…The moisture and ash percentages (Table 4) of the muscle tissues of the animals in the two treatments were close to the rates given by Simões 22 and Tonial 23 in their research on the tilapia muscle tissue. The CP rates at the end of the current experiment were close to those given in the study by Visentainer 24 in juvenile tilapia, with rates ranging between 19.8 and 20.9%.…”
Section: Discussionsupporting
confidence: 79%
“…Several authors confirmed the presence of those essential fatty acids in residues of tilapia (Cengiz, Kan, Kizmaz, Bashan, & Yanar, 2012;Stevanato et al, 2008;Navarro et al, 2012;Tonial, Matsushita, Furuya, Souza, & Visentainer, 2012). The docosahexaenoic acid (DHA) is a very important fatty acid responsible for the physical properties of the brain membranes, the features of their receptors, the cellular interactions and the enzymatic activity (Yehuda, Rabinovitz, Carasso, & Mostofsky, 2002).…”
Section: Resultsmentioning
confidence: 89%
“…The fatty acids considered essential and belonging to the omega 3 family have shown values for α-linolenic (1.12 to 1.87), eicosapentaenoic acid (0.76 to 2.19), and docosahexaenoic acid (0.32 to 0.63). Several authors confirmed the presence of those essential fatty acids in residues of tilapia (CENGIZ et al, 2012;STEVANATO et al, 2008;NAVARRO et al, 2012;TONIAL et al, 2012). Table 1.…”
Section: Fatty Acid Composition In the Adipose Tissue From The Orbitamentioning
confidence: 70%